Reprodução e sexualidade de pessoas que (con)vivem com HIV/AIDS : uma abordagem humanística - Vidal, Eglídia Carla Figueiredo (2008)
The arise of HIV/AIDS and the design of the epidemy demanded changes in the sexual and reproductive health of men and women who live with the virus. The fact that survival and life quality improved with the advent of antiretroviral therapy highlighted the aspect of chronicity of HIV infection, outlining possibilities for affective-sexual and reproductive relationships in this new reality, in a complex scenery that involves concordant and discordant couples in contexts of life similar to non-infected people, in a process of re-signification of HIV/AIDS and of search for control of this pandemy. This study aimed to understand sexual and reproductive experience of people who live with HIV. The Humanistic Nursing Theory by Paterson and Zderad was used as a theoretical and methodological reference. This is a descriptive research with qualitative design, held at the infectology clinic of the School Hospital Santo Inácio, in Juazeiro do Norte-CE. The subjects of the study were 16 people who live with HIV/AIDS, 7 men and 9 women. Data were collected from July through November, 2007, through free observation, analysis of medical records and semi-structured interview. For the testimonies’ analysis the technique of content analysis was adopted, from which emerged three themes: 1. Sexual experience; 2. Reproductive experience, and 3. Marriage Experience. In these themes one identified eleven sub-themes: 1. The condom in sexual intercourses; 2. Changes in desire after the discovery of HIV seropositivity, 3. Changes in sexual practice after the discovery of HIV seropositivity, 4. Contraceptive methods used before the experience and living with HIV/AIDS; 5. The condom as a contraceptive reference and protection in sexual intercourses; 6. Ignorance about the use of other contraceptive methods in HIV infection; 7. Desire to have children; 8. Fear of vertical transmission of HIV; 9. (Lack of) knowledge about prophylactic measures to reduce the vertical transmission of HIV; 10. Modification in marital relationship due to self-care and care with the other; 11. The distrust in the partner because of HIV. Out of the people who experience and live with HIV/AIDS one got different experiences and meanings for sexual and reproductive experiences in complex life sceneries, still permeated by the stigma resulting from AIDS. The subjects of this study lived in marital union ranging from eight months through over fifteen years, eleven of whom lived in conjugal concordant relationship to HIV and five in discordant relationship. We did not notice divergence of data by the variable time of union. We noticed difficult socioeconomic situation and presence of children, including five conceived after the knowledge of HIV, and two women during pregnancy. The time spent living with the infection varied from less than a year to more than eleven years. In half the cases the context of discovery of HIV infection involved the gestational period, the others after opportunistic disease or by convincing of the partner, being a difficult moment due to proved marital infidelity. The results indicated that the condom was not part of their sexual routine until the knowledge of HIV, being the virus a determinant condition for joining the condom. The stability of the conjugal relationship served in the pre-infection phase as one of the factors that contributed to the non-use of condoms, causing larger contexts of vulnerability, where the genre appears as the main factor. The use of male condoms, after seroconversion, highlighted the difficulties in adhesion, especially among those who had never experienced this method of protection, revealing possible awareness of the need to adapt to the device in sexual intercourse, which is re-signified for these people. However, there is a bigger confrontation for the maintenance of the prevention practice by the use of condoms in discordant couples. The discovery of HIV seropositivity demanded changes in sexual routine, showing a decrease in sexual desire and change in sexual practices, with different aspects for men and women surveyed. There were changes in routine of contraceptive methods used before the seroconversion, using new methods, especially the male condom, in the presence of HIV. We highlighted the lack of knowledge of alternatives contraceptive methods face to HIV infection and AIDS. The desire to have children was observed in men and women, and the fear of vertical transmission appears as a strong determinant to deny that choice, with the lack of prophylactic measures to reduce vertical transmission. The difficulties in fighting against HIV/AIDS require changes in the daily life of the couple, highlighting a bilateral marital behavior of care for the other in an ambiguous relationship because of distrust with the knowledge of HIV infection. This study allowed us to realize that we must open channels of dialogue about sexual and reproductive experiences, stressing the important dimension that is given to the relationships between professionals and patients, as participants in the search of health promotion in a reality still in construction, of re-signification of life, of relationships and health. The gestational period is highlighted as an important moment for the diagnosis of HIV infection, to advise the recommendations and to reduce vertical transmission, beginning with early prevention of vertical transmission, through humanized care, free of judgments and prejudice. The assistance in sexual and reproductive health for people living with HIV demands several questions and challenges, but it points mainly to the need of integral and non-dichotomous assistance, where prevention and treatment work together, recognizing limits, possibilities, aims and priorities, in the individualization of human care.